Use of electrochemotherapy in women with vulvar cancer to improve quality-of-life in the palliative setting: a meta-analysis. Issue 1 (3rd December 2019) - Tranoulis, Anastasios; Georgiou, Dimitra; Founta, Christina; Mehra, Gautam; Sayasneh, Ahmad; Nath, Rahul
Abstract : Introduction: Electrochemotherapy involves the use of transient tumor permeabilization via electric pulses in combination with low-dose chemotherapeutic agents. It has recently emerged as an alternative treatment modality in vulvar cancer. The aim of this meta-analysis was to ascertain the effectiveness of electrochemotherapy in the context of palliative care. Methods: The following databases were searched: MEDLINE, Scopus, and Cochrane Database, to identify all registered articles pertaining to palliative vulvar cancer treatment with electrochemotherapy from inception until August 2019, in line with PRISMA guidelines. A single-proportion meta-analysis was performed for the outcomes of overall response, complete response, partial response, stable disease, and progressive disease raterespectively, using the random-effect model. Sensitivity analysis was performed to address heterogeneity. Results: Four studies were included totaling 104 women. The studies were of moderate quality. Pooled results from four studies rendered a summary proportion of 78.8% (95% CI 70.4% to 86.1%) for the outcome of overall response. The median age ranged between 68 and 85 years. The sample size per study ranged between eight and 61 women. The tumors' histological types included: squamous-cell carcinoma (96.2%), Paget's disease (2.9%), and malignant melanoma (0.9%). A total of 65 patients (62.5%) presented with a single nodule, whilst 39 patients (37.5%) presented with multiple nodules. Eighty-nine women (85.6%) were previously submitted to other treatment modalities. The overall response rate ranged from 73.2% to 80.9%. The pooled proportion for the outcomes of complete and partial response rate was 48.7% (95% CI 30.74% to 61.5%) and 30.2% (95% CI 21.7% to 39.4%), respectively. The follow-up ranged from 1 to 51 months. No severe adverse effects were reported. The safety profile of electrochemotherapy was favorable. Conclusions: Electrochemotherapy is an effective and minimally invasive treatment modality in the palliative care management of patients with vulvar cancer. The effective control of vulvar tumors by electrochemotherapy may contribute to improvement of quality-of-life. In light of the moderate quality of evidence, a multi-center cooperation is warranted to confirm its palliative benefit.